Preoperative and postoperative hemoglobin estimation in hypertensive disorders of pregnancy undergoing cesarean section - Sabina Parveen; Meera; Chennupati Lakshmi Sravya (Al Ameen Medical College, 2024)
Aim: To study preoperative and post operative hemoglobin in patients with hypertensive disease of pregnancy under goining Cesarean Section. Methods: This is a retrospective study conducted in Al-Ameen Medical College, Hospital & research center Vijayapura, over a period of one year from Jan 2023 to Dec 2023. Required data was collected and hemoglobin estimation was done using CBC auto analyzer. Pregnant patients with hypertensive disease of pregnancy who had systolic blood pressure ≥ 140mmhg or diastolic blood pressure ≥90mmhg were studied. Blood pressure was measured in sitting position arm at the level of heart. Proteinuria was determined by dipstick method. Statistical analysis results are represented as frequency and percentage. The data analysis was done using SPSS v 24. Results: We had a total of 109 patients with hypertensive disease of pregnancy over a period of one year of which 12 patients had vaginal delivery and 97 patients under went Cesarean section,3 patients were excluded as they did not meet inclusion criteria. Of 94 patients with hypertensive disease of pregnancy, the indication for cesarean section were severe preeclampsia, eclampsia, cephalopelvic disproportion, failed induction, severe oligohydromnios, fetal distress, postdated, breech, intrauterine-growth restriction, previous 2 lower segment cesarean section. Hemoglobin estimation was done preoperatively and after 24hrs post operatively. The mean gestational age is 38 weeks, mean birth weight of babies is 2.7Kg. The mean preoperative hemoglobin in hypertensive disease of pregnancy patient is 11.3(SD-1.2); and postoperative hemoglobin is 10.6(SD-1.2) and is statistically significant (p<0.0001). Conclusion: Blood loss in pregnant women with hypertensive disease of pregnancy undergoing cesarean section though statistically significant does not require any intervention in postoperative period. Blood loss is clinically insignificant.